PENGARUH TUJUAN BERPRESTASI TERHADAP KETERAMPILAN METAKOGNISI SISWA DALAM PEMECAHAN MASALAH KIMIA - Khairiatul Muna (Universitas Lambung Mangkurat, 2017)
Abstract. Metacognitive skills is one of the determinants of student success in problem solving. The size of the effect of metacognitive skills in problem solving was also effected directly or indirectly by one’s motivation. Component of motivations that also giving the effect in the use of metacognitive skills in problem solving is the students' achievement goal. Achievement goal that became the research in this article was the mastery goal. In order to know the effect of the achievement goal on metacognitive skills in chemical problem solving, then conducted research that related to metacognition and motivation, especially on chemical equilibrium material. The results presented in this article are a part of major reserach using correlational descriptive studies. The population of the research was the students of class XI IPA SMAN 2 Banjarmasin, with the sample of the research amounted to 33 students. The research data were collected using essay tests, metacognitive skill questionnaires, SMTSL questionnaires and student interviews. Based on data analysis result with statistical technique of product moment correlation shows that there is a significant positive correlation between student achievement goals with metacognition skills in chemical equilibrium problem solving, with correlation value (r) obtained for +0.516. Students with the achievement goal especially the mastery goal will focus on learning and mastery of learning materials, the use of metacognition and good performance in problem solving.Keywords: effect, achievement goal, metacognitive skills, chemical equilibrium, correlational study.